An Examination of the Prescription Renewal Process and Implications for Primary Care Physicians and Community Pharmacists. (April 2020) - Pattin, Anthony J.; Devore, Nathan; Fowler, Jonathan; Weldy, David
In physician practices and pharmacies, staff members work to process prescription renewals so that patients receive a steady supply of medications. These functions are essential to ensure patients have continuous access to medications and remain adherent to prescribed therapies. Despite the incorporation of e-prescribing software programs to ease management of these processes, barriers to effective management of the prescription renewal process exist. Mismanagement of pharmacy adherence programs can ultimately lead to patients receiving inappropriate medications and excessive use of staff resources. The objective of this article is to examine the prescription renewal process in both the primary care setting and the pharmacy and report challenges associated with the process. A literature review was conducted to find studies that describe pharmacists' and physicians' handlings of prescription renewals, use of e-prescribing software, and benefits and barriers to using these technologies. Although studies report e-prescribing software improves efficiency in the prescription renewal process, there is a need to reduce technological problems that create challenges in use. It is recommended that staff within physician practices and pharmacies standardize prescription renewal processes and educate patients about the prescription renewal process.